Fluorescent vesicles formed by simple surfactants induced by oppositely-charged carbon quantum dots. Issue 81 (8th September 2016) - Sun, Xiaofeng; Zhang, Qinghong; Yin, Keyang; Zhou, Shengju; Li, Hongguang
Abstract : Fluorescent vesicles can be constructed by mixing oppositely-charged CQDs and simple surfactants in water. Abstract : We show for the first time that stable fluorescent vesicles can be constructed by mixing oppositely-charged carbon quantum dots (CQDs) and simple surfactants in water, and can be potentially used as a new generation of biomarkers and drug delivery vehicles.